A diagnosis method based on graph neural networks embedded with multirelationships of intrinsic mode functions for multiple mechanical faults - Bin Wang; Manyi Wang; Yadong Xu; Liangkuan Wang; Shiyu Chen; Xuanshi Chen (Defence Technology)
Fault diagnosis occupies a pivotal position within the domain of machine and equipment management. Existing methods, however, often exhibit limitations in their scope of application, typically focusing on specific types of signals or faults in individual mechanical components while being constrained by data types and inherent characteristics. To address the limitations of existing methods, we propose a fault diagnosis method based on graph neural networks (GNNs) embedded with multirelationships of intrinsic mode functions (MIMF). The approach introduces a novel graph topological structure constructed from the features of intrinsic mode functions (IMFs) of monitored signals and their multirelationships. Additionally, a graph-level based fault diagnosis network model is designed to enhance feature learning capabilities for graph samples and enable flexible application across diverse signal sources and devices. Experimental validation with datasets including independent vibration signals for gear fault detection, mixed vibration signals for concurrent gear and bearing faults, and pressure signals for hydraulic cylinder leakage characterization demonstrates the model's adaptability and superior diagnostic accuracy across various types of signals and mechanical systems.